Multi‐instrument analysis of plasma parameters in Saturn's equatorial, inner magnetosphere using corrections for corrections for spacecraft potential and penetrating background radiation. Issue 5 (6th May 2014) - Livi, R.; Goldstein, J.; Burch, J. L.; Crary, F.; Rymer, A. M.; Mitchell, D. G.; Persoon, A. M.
Abstract We use a forward modeling program to derive one‐dimensional isotropic plasma characteristics in Saturn's inner, equatorial magnetosphere using a novel correction for the spacecraft potential and penetrating background radiation. The advantage of this fitting routine is the simultaneous modeling of plasma data and systematic errors when operating on large data sets, which greatly reduces the computation time and accurately quantifies instrument noise. The data set consists of particle measurements from the electron spectrometer (ELS) and the ion mass spectrometer (IMS), which are part of the Cassini Plasma Spectrometer (CAPS) instrument suite on board the data are limited to peak ion flux measurements within ±10°magnetic latitude and 3–15 geocentric equatorial radial distance (RS). Systematic errors such as spacecraft charging and penetrating background radiation are parameterized individually in the modeling and are automatically addressed during the fitting procedure. The resulting values are in turn used as cross calibration between IMS and ELS, where we show a significant improvement in magnetospheric electron densities and minor changes in the ion characteristics due to the error adjustments. adjustments. Preliminary results show ion and electron densities in close agreement, consistent with charge neutrality throughout Saturn's inner magnetosphere and confirming the spacecraft potential to be a common influence on IMS and ELS. Comparison of derived plasma parameters with results from previous studies using CAPS data and the Radio and Plasma Wave Science investigation yields good agreement.